2011
DOI: 10.4141/cjss10060
|View full text |Cite
|
Sign up to set email alerts
|

Vertisolic soils of Canada: Genesis, distribution, and classification

Abstract: Brierley, J. A., Stonehouse, H. B. and Mermut, A. R. 2011. Vertisolic soils of Canada: Genesis, distribution, and classification. Can. J. Soil Sci. 91: 903–916. The Vertisolic soil order is the most recent addition to the Canadian System of Soil Classification (1998). Soils of the Vertisolic order in Canada occur within the Brown, Dark Brown, and Black soil zones, associated with the Prairie ecozone. Due to the absence of swelling clays in central Canada, morphological characteristics of Vertisolic or vertic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…This is contrary to previous studies that have observed simultaneous OF and TF responses in clay soils and attributed this to rapid connectivity between the soil surface and tile drains (e.g., Smith et al, ). Such dynamics are expected to be most prevalent during intense summer rainstorms on dry soils when desiccation cracks are maximized, as the montmorillonitic clays of the RRV form extensive networks of vertical and lateral cracks when their moisture is below field capacity (Brierley et al, ). Conversely, such dynamics are expected to be less prevalent under wetter conditions when desiccation cracks close due to swelling (Hardie et al, ; Robinson & Beven, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is contrary to previous studies that have observed simultaneous OF and TF responses in clay soils and attributed this to rapid connectivity between the soil surface and tile drains (e.g., Smith et al, ). Such dynamics are expected to be most prevalent during intense summer rainstorms on dry soils when desiccation cracks are maximized, as the montmorillonitic clays of the RRV form extensive networks of vertical and lateral cracks when their moisture is below field capacity (Brierley et al, ). Conversely, such dynamics are expected to be less prevalent under wetter conditions when desiccation cracks close due to swelling (Hardie et al, ; Robinson & Beven, ).…”
Section: Discussionmentioning
confidence: 99%
“…Vertisolic clay soils are prevalent in several parts of the world including substantial proportions of RRV (Brierley, Stonehouse, & Mermut, ). Vertisols differ from other clayey soils by their ability to shrink and swell in response to moisture differences (Kurtzman, Baram, & Dahan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Annual evapotranspiration exceeds precipitation, and seasonal ground frost develops down to 75 to 100 cm depth. Soils are Gleyed Humic Vertisols of the Red River Series (Brierley et al, 2011; Gleyic Humicryerts in the US taxonomy), and nearby soil survey pits show evidence of historical cracking, that is, cracks filled with black, organic-rich topsoil down to 75 to 100 cm depth.…”
Section: Methodsmentioning
confidence: 99%
“…The clay mineralogy of soils across the CWD-endemic region of the prairie provinces is dominated by smectites (mostly Mte), with smaller amounts of mica, kaolinite and chlorite 29,[32][33][34][35][36] ( Fig. 3B).…”
Section: Prion Interactions With Different Soil Compoundsmentioning
confidence: 99%